Efficacy of bentonite and fumonisin esterase in mitigating the effects of aflatoxins and fumonisins in two Kenyan cattle breeds - Kemboi, D.; Antonissen, G.; Ochieng, P.; Croubels, S.; Baere, S. de; Scippo, M.-L.; Okoth, Sheila A.; Kang'ethe, Erastus K.; Faas, J.; Doupovec, B.; Lindahl, Johanna F.; Gathumbi, J. (American Chemical Society, 2023)
The objective of the study was to investigate the efficacy of bentonite and fumonisin esterase, separately or combined, in mitigating the effects of aflatoxins (AF) and fumonisins (FUM) in Boran and Friesian-Boran crossbreed cattle. These effects were studied by measuring mycotoxins, their metabolites, and biomarkers that relate to animal health, productivity, and food safety. The study was divided into three experiments each lasting for 2 weeks. Cows in experiment 1 received in random order aflatoxin B1 (AFB1) [788 μg/cow/day (69.7 μg/kg dry matter intake (DMI)) for Borans and 2,310 μg/cow/day (154 μg/kg DMI) for crossbreeds], bentonite (60 g/cow/day), or both AFB1 and bentonite. Boran cows in experiment 2 received in random order FUM (12.4 mg/cow/day (1.1 mg/kg DMI)), fumonisin esterase (120 U/cow/day), or both FUM and fumonisin esterase. Boran cows in experiment 3 received in random order AFB1 (952 μg/cow/day (84.2 μg/kg DMI)) + FUM (30.4 mg/cow/day (2.7 mg/kg DMI)), bentonite (60 g/cow/day) + fumonisin esterase (120 U/cow/day), or both AFB1 + FUM and bentonite + fumonisin esterase. Feeding AFB1 and/or FUM contaminated feed with or without the addition of the detoxifiers for 14 days did not affect DMI, milk composition, hematology, and blood biochemical parameters. The addition of bentonite in a diet contaminated with AFB1 led to a decrease in milk aflatoxin M1 (AFM1) concentration of 30% and 43%, with the carry-over subsequently decreasing from 0.35% to 0.20% and 0.08% to 0.06% for crosses and Borans, respectively. No significant change was observed in the sphinganine/sphingosine (Sa/So) ratio following feeding with FUM alone or in combination with fumonisin esterase; however, the ability of fumonisin esterase to hydrolyze FUM into less toxic fully hydrolyzed FUM and partially hydrolyzed FUM was evident in the rumen fluid and feces. These results indicate bentonite was effective in decreasing AFM1 concentration in milk, and AFB1 and AFM1 in plasma, while fumonisin esterase can convert FUM into less toxic metabolites and can be a suitable addition to feed cocontaminated with AFB1 and FUM.